Contributions to an additive method for manufacturing solderless assembly for electronics. Issue 1 (1st September 2022) - Varzaru, G; Savu, M; Mihailescu, B; Ionescu, C; Branzei, M
Abstract: The demand for more reliable electronic and affordable products has generated innovative activities in electronic packaging that have highlighted the great benefits of additive technologies. This approach requires new equipment for the electronic assembly line, such as 3D-printer, but especially new materials. Within the additive techniques, one that still keeps the assembly line is the Occam Process. This disruptive concept eliminates the use of solder alloy, and combines into one two technological processes: the manufacture of the printed circuit board and the electronic assembly. Following this concept, the paper presents the result of the research of a couple of electrically conductive adhesive materials and a method for their qualification in the manufacture of solderless electronic modules that can handle ultra high-frequency and microwave signals. A practical solution is to compare the frequency behavior of two identical test structures, one made by the adhesive material, and the other by copper. The comparative analysis showed that electrically conductive adhesives present a slightly better response at high frequencies than copper in terms of insertion loss and return loss in the range 0 to 10 GHz; the adhesive replacement for solder alloy to connect temperature-sensitive components operating at high frequency is a good alternative.